Primary Vaginal Leiomyosarcoma Mimicking Bartholin's Cyst - Deepthy Balakrishnan; Saubhagya Kumar Jena; Pritinanda Mishra (Wolters Kluwer Medknow Publications, 2024)
Leiomyosarcomas (LMS) arise from smooth muscle cells with more predilection to the uterus, abdomen, retroperitoneum, and blood vessels. LMS of vagina is very rare and usually presents in the early stage as an asymptomatic mobile mass with no clinical features of malignancy and gives the appearance of a benign lesion which can easily be mistaken for a Bartholin's cyst or a vaginal fibroid. The chances of metastasis in LMS are high with poor survival rates. Histopathology confirms the diagnosis and treatment still remains controversial due to less data on this rare malignancy. Even though there is no evidence that leiomyoma can transform into LMS, benign-looking vaginal fibroids need to be resected to avoid misdiagnosis of LMS. We present a case of vaginal LMS which was mistaken to be Bartholin's cyst due to the lack of knowledge of this aggressive tumor and further management.